Typical Utilization of Gestalt Grouping Cues in Shape Perception by Persons with Autism Spectrum Disorder. (December 2019) - Hadad, Bat Sheva; Russo, Natalie; Kimchi, Ruth; Babineau, Vanessa; Burack, Jacob A.
The common finding of better locally oriented perception among persons with autism spectrum disorder (ASD) is based on evidence from paradigms in which hierarchical stimuli are used to pit local and global processes against one another. However, in most cases, determining whether group differences reflect reduced global processing, enhanced local processing, or both is difficult. To provide more conclusive evidence for global perception in ASD, we examined shape formation and sensitivity to Gestalt heuristics. Children with persons with ASD and mental age matched typically developing children completed tasks in which the organization of contour segments into a shape was likely to depend on utilizing cues of closure, spatial proximity, and collinearity. In Experiment 1, search efficiency was measured, with the efficiency of the global organization indicated by the slope of the best-fitting linear reaction-time function over the number of presented items. In Experiment 2, contour integration task was administered, while Gestalt cues and the contour to background spacing ratio were manipulated independently. The findings indicated typical shape formation among the persons with ASD. Furthermore, certain interactive relations between Gestalt grouping cues that are known to govern shape formation in typically developing individuals determined the extraction of the global shape among the participants with ASD.